USE OF BIOSTIMULATE FOR BREAK DORMANCY OF APPLE TREE CV. CASTEL GALA - BOTELHO, Renato Vasconcelos (Scientia Agraria, 2008)
A trial was carried out in an orchard of apple tree cv. Castel Gala, aiming to verify the effect of Stimulate®, product containing plant regulators and traces of quelated mineral, on budbreak dormancy. In August 28th of 2007, the following doses of Stimulate® were sprayed at the “drip point”: 0, 5, 10 and 1.5 mL L-1. All treatments were added of 10 mL L-1 plant oil (Natur’Óleo, Stoller do Brasil Ltda.). The experimental design was completely randomized blocks and split pot factorial scheme (treatments x time), with four treatments, five replications and one-plant experimental plot. Three branches per plant were evaluated at 0, 14, 28, 42 and 56 days after treatments for bud sprouting percentage. The number of fruits by trunk transversal section was calculated (fruits cm-2). All treatments with Stimulate® improved bud sprouting percentage of apple trees cv. Castel Gala, compared to the control. The most effective treatment was 5 mL L-1 Stimulate® getting 50.7% bud sprouting, while control attained only 24.7%. Nevertheless, 15 mL L-1 Stimulate® decreased number of fruits cm-2.